On the motion of mechanical systems with unilateral constraints - Sanh, Do (Vietnam Journal of Mechanics, 1984)
The motion of the system with unilateral constraints being imposed may be divised into positions, so that in certain positions the constraint is taut and the motion occurs as if the constraint was bilateral and in other positions the constraint is not taut and the motion occurs as if there was no such constraint. In the present paper two problems are discussed : 1. To determine the constant of time along with the positions and the velocities of the system when the system has just been released from the constraint. 2. To write the equations of motion of the system when the system has been released from the constraint.